Ты умеешь хранить секреты?: [роман] / Софи Кинселла - Кинселла Софи (Femina, 2004)
Экземпляры: ЧЗ (20181113) / Инвентарный номер: 38875 / Цена: 96. 47 / Сис.шифр: 84 (4Вел) / Авт.знак: К 41 / ГРНТИ: 17.82 / ББК: 84(4Вел)